2016
DOI: 10.1111/resp.12862
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of incidence and outcome of acute exacerbation in idiopathic interstitial pneumonia

Abstract: Background and objective: Acute exacerbations (AEs) of idiopathic pulmonary fibrosis (IPF) and other idiopathic interstitial pneumonia (IIP) have a poor prognosis. This study aims to clarify the incidence and prognosis of AE in IPF and the other IIP. Methods: A total of 229 patients were enrolled, of whom 92 had IPF and 137 had 'IIP other than IPF' based on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 29 publications
2
48
2
Order By: Relevance
“…In general, fibrotic NSIP, CHP, CTD‐ILD and UC‐ILD are the most frequent diagnoses in the differential with IPF. Previously published data showed that the frequencies of AE in these categories were lower than that of AE‐IPF . In our study, there was no significant difference in the frequency and short‐term outcomes of AE among FILD subtypes.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In general, fibrotic NSIP, CHP, CTD‐ILD and UC‐ILD are the most frequent diagnoses in the differential with IPF. Previously published data showed that the frequencies of AE in these categories were lower than that of AE‐IPF . In our study, there was no significant difference in the frequency and short‐term outcomes of AE among FILD subtypes.…”
Section: Discussioncontrasting
confidence: 59%
“…This group includes the fibrotic form of non‐specific interstitial pneumonia (NSIP), chronic (fibrotic) hypersensitivity pneumonitis (CHP), connective tissue disease‐associated ILD (CTD‐ILD), unclassifiable ILD (UC‐ILD) and others. Currently, there are limited data regarding the frequency and prognosis of AE in patients with FILD . The aim of this study is to compare the incidence, risk factors and outcomes between AE in IPF and non‐IPF forms of FILD.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the fibrotic ILDs, AE accounts for significant morbidity and mortality. [80][81][82] Although no consensus definition for AE-ILD exists, the generally accepted criteria are extrapolated from the IPF population given the similarities in presentation. AE is generally characterized by acutely (typically < 1 month) worsening dyspnea and parenchymal infiltrates on imaging.…”
Section: Acute Exacerbation In Ildsmentioning
confidence: 99%
“…have been recently updated. AE is the most common immediate cause of death in IPF, and improved management of AE‐IPF purportedly leads to a better disease prognosis. In addition, AE reportedly occurs in patients with idiopathic interstitial pneumonias (IIP) other than IPF (non‐IPF) …”
Section: Introductionmentioning
confidence: 99%